The Fight is on in Texas - Robinson, Edward J. (Abilene Christian University Press, 2023)
This groundbreaking work draws upon congregational histories and other primary sources to chronicle for the first time the story of African American Churches of Christ in Texas. Emerging out of the nineteenth-century Stone-Campbell Restoration Movement, the African American churches inherited from their white mentors both a Biblicist theology and a feisty spirit. Their “fight" was against religious error and in support of the true church as they understood it. Out of that “fight" emerged a growing network of congregations that by the mid-twentieth century reached throughout Texas. This book lifts out of obscurity the African American Christians who joined Ramsey’s “fight …out West" and who made black Churches of Christ in Texas what they are today.